Pandemic Preparedness: Developing Vaccines and Therapeutic Antibodies For COVID-19 - Sempowski, Gregory D. (Cell, 2020)
The SARS-CoV-2 pandemic that causes COVID-19 respiratory syndrome has caused global public health and economic crises, necessitating rapid development of vaccines and therapeutic countermeasures. The world-wide response to the COVID-19 pandemic has been unprecedented with government, academic, and private partnerships working together to rapidly develop vaccine and antibody countermeasures. Many of the technologies being used are derived from prior government-academic partnerships for response to other emerging infections.